1997
DOI: 10.1111/j.1399-302x.1997.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological study of lesions induced by Porphyromonas gingivalis in a murine model

Abstract: A previous study used a mouse model to demonstrate protection after challenge with Porphyromonas gingivalis ATCC 33277. In the present study, this same model was used to determine the phenotype of cells recruited into the lesions during the course of the protective immune response after immunization with this periodontal pathogen. BALB/c mice were immunized with 100 micrograms of P. gingivalis outer membrane antigens per mouse weekly for 3 weeks followed by challenge with live organisms 3 weeks after the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Previous studies using this model showed that the induction of an immune response and subsequent healing were CD4 cell-dependent, 20,21 which supports the present findings. The induction of a Th1-like response to P. gingivalis in rats has also been reported by Katz and Michalek.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies using this model showed that the induction of an immune response and subsequent healing were CD4 cell-dependent, 20,21 which supports the present findings. The induction of a Th1-like response to P. gingivalis in rats has also been reported by Katz and Michalek.…”
Section: Discussionsupporting
confidence: 94%
“…The alum‐based adjuvant produced the largest increase in leukocyte numbers and its effect lasted longer than the IFA. Similarly, Gemmell et al (1997) showed an increased PMN accumulation, in an abscess model after immunization with P. gingivalis. The mechanism involved in this increased PMN recruitment is probably mediated via an increase in the accumulation of chemotactic factors including those derived from activated complement fragments.…”
Section: Discussionmentioning
confidence: 80%
“…CD4 + and CD8 + T‐cell subsets, CD14 + cells (activated monocytes/macrophages and dendritic cells but not unstimulated macrophages, dendritic cells, neutrophils or blood monocytes) and CD19 + B cells (but not terminally differentiated plasma cells) were labeled using an avidin–biotin immunoperoxidase method described previously (9). Briefly, after rehydration in phosphate‐buffered saline pH 7.2, the sections were incubated with rat anti‐mouse CD4 (L3T4), CD8a (Ly‐2), CD14 or CD19 (PharMingen, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%